2017
DOI: 10.1016/j.jeem.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Water scarcity and rioting: Disaggregated evidence from Sub-Saharan Africa

Abstract: It is often purported that unusually dry conditions provoke riots by intensifying the competition for water. The present paper explores this hypothesis, using data from Sub-Saharan Africa. We rely on monthly data at the cell level (0:5 0:5 degrees), an approach that is tailored to the fact that riots are short-lived and local events. Using a drought index to proxy for deviations of the actual climatic water balance from the normal one, we …nd that a one-standard-deviation fall in the index (signaling drier con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 33 publications
4
42
1
Order By: Relevance
“…Our results also add new micro evidence to the literature on the determinants of social conflicts (e.g., Bellemare 2015), and on the relationship between weather anomalies and human conflicts (e.g., studies by Miguel, Satyanath, and Sergenti 2004; Burke et al 2009; Jia 2014; Couttenier and Soubeyran 2014; Maystadt and Ecker 2014; Almer, Laurent‐Lucchetti, and Oechslin 2017; Harari and La Ferrara 2018). It is generally found that rainfall anomalies are positively correlated with the occurrence of large‐scale conflicts .…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Our results also add new micro evidence to the literature on the determinants of social conflicts (e.g., Bellemare 2015), and on the relationship between weather anomalies and human conflicts (e.g., studies by Miguel, Satyanath, and Sergenti 2004; Burke et al 2009; Jia 2014; Couttenier and Soubeyran 2014; Maystadt and Ecker 2014; Almer, Laurent‐Lucchetti, and Oechslin 2017; Harari and La Ferrara 2018). It is generally found that rainfall anomalies are positively correlated with the occurrence of large‐scale conflicts .…”
supporting
confidence: 75%
“…Following the recent literature on water scarcity and conflicts (e.g., Couttenier and Soubeyran 2014; Almer, Laurent‐Lucchetti, and Oechslin 2017; Harari and La Ferrara 2018) we adopt a finer instrument to measure water availability. Our benchmark indicator of water scarcity, denoted as SPEI Shock is defined as the fraction of the rainy seasons (spring and summer) during which the SPEI index was below its mean by half a standard deviation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impacts of such water deficits go beyond water access. They impair biodiversity, public health, education, and business (Almer et al, 2017;Freire-González et al, 2017;Gleick, 2018). For instance, Damania et al (2017) estimate a single water outage can reduce a firm's revenue by more than 8% or as much as 35% in the informal sector.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide deficiency of clean freshwater causes sanitation problems, food shortage and sometimes even conflicts [1][2][3]. UN's sustainable development goal (SDG), number 6 aim to ensure access to water and sanitation for all [4]-a goal currently far from met.…”
Section: Introductionmentioning
confidence: 99%